Internal computational dosimetry of natural cisplatin activated in neutron flux (Brazilian Journal of Radiation Sciences, 2022)
Cisplatin is currently used in the treatment of numerous types of tumors, such as head and neck, esophagus, bladder, testicle. However, the cisplatin use is limited due to its cytotoxic effects. Thus, considering its side effects, lines of research are looking for new technologies to reduce the dose of the chemotherapeutic agent needed to control the disease, which may reduce these side effects. The objective of this work was to perform the internal dosimetry of 191Pt radioisotope derived from the activation of natural cisplatin, thus contributing to the evaluation of the feasibility of a new radiopharmaceutical of natural cisplatin activated by neutrons for application in humans. The dosimetry was obtained with Monte Carlo simulations using two stylized phantoms developed by authors Dragana Krstic and Dragoslav Nikezic and the ICRP adult reference voxelized phantoms. As results, differences were observed between absorbed doses estimated using the two types of phantoms (analytical and voxelized). The highest doses noted in the analytical phantom were in the kidneys (1.58 mGy/MBq), liver (1.32 mGy/MBq), spleen (1.23 mGy/MBq), bladder wall (0.74 mGy/MBq), gallbladder wall (0.56 mGy/MBq), pancreas (0.41 mGy/MBq), and adrenals (0.39 mGy/MBq). For the voxelized phantoms, the highest doses obtained were: kidneys (1.46 mGy/MBq), spleen (1.13 mGy/MBq), liver (1.11 mGy/MBq), gallbladder wall (0.47 mGy/MBq), adrenals (0.41 mGy/MBq), bladder wall (0.36 mGy/MBq), and pancreas (0.29 mGy/MBq). The effective dose was 0.22 mSv/MBq for the analytical phantom, a value similar to that obtained with voxelized phantoms (0.20 mSv/MBq).
Keywords: Dosimetria interna; Cisplatina